PENGARUH PROMOSI, TERHADAP KEPUTUSAN PENGGUNAAN LAYANAN DIGITAL DIMEDIASI OLEH PENGETAHUAN KONSUMEN DAN KEPERCAYAAN KONSUMEN DI BANK SUMSEL BABEL CABANG PRABUMULIH - Omar Hendro; Diah Isnaini Asiati; Dwi Puspita Sari (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2020)
This study aims to find out "The Influence of Promotion, Against the Decision on the Use of Digital Services Mediated by Consumer Knowledge and Consumer Confidence in the Babylon Bank of South Sumatra Branch". Problem formulation is a problem that will be answered by the research objectives. This study uses a statistical analysis tool that is multiple linear regression. The results of the calculation, the influence of each construct on the construct; first, Promotion has a positive and significant effect on Consumer Trust. The results of data analysis obtained a t-value of 27,182 with a t-table value of 1,965973. Second, Promotion has a significant effect on Consumer Knowledge. The results of data analysis obtained a t-value of 25.218 with a t-table value of 1.965973. This means that the Promotion variable has a significant effect on the Consumer Knowledge variable. Third, Consumer Trust has a positive and significant effect on Decision of Use. The results of data analysis obtained a t-value of 4.169 with a t-table value of 1.965973. Fourth, Consumer Knowledge has a positive and significant effect on Decision of Use. The results of data analysis obtained a value of t-value of 3.561 with a t-table value of 1.965973. Fifth, Promotion has a positive and significant effect on the Decision of Use. The results of data analysis obtained a t-value of 3.342 with a t-table value of 1.965973. This means that the Promotion variable has a positive and significant effect on the Decision Use variable